A Brush Seals Program Modeling and Developments. (1998) - Hendricks Hendricks, Robert C. Robert C.; Flower Flower, Ralph Ralph; Howe Howe, Harold Harold
Abstract : Some events of a US Army/NASA Lewis Research Center brush seals program are reviewed, and the development of ceramic brush seals is described. Some preliminary roomtemperature flow data are modeled and compare favorably to the results of Ergun.